Activation of Hypothalamic AMP‐Activated Protein Kinase Ameliorates Metabolic Complications of Experimental Arthritis. Issue 2 (29th December 2021) - Seoane‐Collazo, Patricia; Rial‐Pensado, Eva; Estévez‐Salguero, Ánxela; Milbank, Edward; García‐Caballero, Lucía; Ríos, Marcos; Liñares‐Pose, Laura; Scotece, Morena; Gallego, Rosalía; Fernández‐Real, José Manuel; Nogueiras, Rubén; Diéguez, Carlos; et al.
Abstract : Objective: To investigate whether thermogenesis and the hypothalamus may be involved in the physiopathology of experimental arthritis (EA). Methods: EA was induced in male Lewis rats by intradermal injection of Freund's complete adjuvant (CFA). Food intake, body weight, plasma cytokines, thermographic analysis, gene and protein expression of thermogenic markers in brown adipose tissue (BAT) and white adipose tissue (WAT), and hypothalamic AMP‐activated protein kinase (AMPK) were analyzed. Virogenetic activation of hypothalamic AMPK was performed. Results: We first demonstrated that EA was associated with increased BAT thermogenesis and browning of subcutaneous WAT leading to elevated energy expenditure. Moreover, rats experiencing EA showed inhibition of hypothalamic AMPK, a canonical energy sensor modulating energy homeostasis at the central level. Notably, specific genetic activation of AMPK in the ventromedial nucleus of the hypothalamus (a key site modulating energy metabolism) reversed the effect of EA on energy balance, brown fat, and browning, as well as promoting amelioration of synovial inflammation in experimental arthritis. Conclusion: Overall, these data indicate that EA promotes a central catabolic state that can be targeted and reversed by the activation of hypothalamic AMPK. This might provide new therapeutic alternatives to treat rheumatoid arthritis (RA)–associated metabolic comorbidities, improving the overall prognosis in patients with RA.